Fluoride content of solid foods impacts daily intake - Rankin, Scott J. (J Public Health Dent, 2011)
OBJECTIVE: To determine the amount of fluoride received from solid foods for a cohort of children. METHODS: Parents were asked to complete questionnaires for the preceding week and dietary diaries for 3 days for their children. Data collected at 6, 9, 12, 16, 20, 24, 36, 48, and 60 months were analyzed cross-sectionally. RESULTS: At 6 months of age, children ingested an estimated mean of 8 percent of dietary fluoride from solid foods. At 12 months of age, children ingested an estimated 39 percent of dietary fluoride from solid foods. Although the percentage of fluoride intake from solid foods stabilized from 24 to 60 months (means of 36–39 percent), some children received as much as 85–88 percent of their dietary fluoride from solid foods. CONCLUSIONS: Some children receive a substantial portion of dietary fluoride from solid foods.